2019
DOI: 10.3389/fpsyg.2019.00946
|View full text |Cite
|
Sign up to set email alerts
|

No Intentions in the Brain: A Wittgensteinian Perspective on the Science of Intention

Abstract: In their paper “Why we may not find intentions in the brain,” Uithol et al. (2014) convincingly argue that “the processes underlying action initiation and control are considerably more dynamic and context sensitive than the concept of intention can allow for.” Their paper could be seen as a critical note to the widespread tendency to search for identifiable neurocorrelates of mental concepts. Their more specific suggestion is that the absence of clear neural correlates undermines the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
6
0
1
Order By: Relevance
“…However, it is important to keep in mind that there may be relevant studies that were not identified for this review, as intention is a difficult concept to cover completely in database searches. Even so, it is remarkable that intention-a concept that was integrated into research on human behaviour a half century ago (Rossetti et al, 2014)has barely been used since then regarding RTW among individuals on sick leave due to CMDs. This may be due to the abstractness of the concept, which makes it difficult to capture in an adequate manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to keep in mind that there may be relevant studies that were not identified for this review, as intention is a difficult concept to cover completely in database searches. Even so, it is remarkable that intention-a concept that was integrated into research on human behaviour a half century ago (Rossetti et al, 2014)has barely been used since then regarding RTW among individuals on sick leave due to CMDs. This may be due to the abstractness of the concept, which makes it difficult to capture in an adequate manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, intention has been shown to be an essential aspect of various health behaviours (Asare, 2015;McDermott et al, 2015), and also RTW after sick leave for musculoskeletal injuries (Dunstan et al, 2013). The roots of studying intention can be | 603 HEDLUND found in the 1970s (Rossetti et al, 2014), when psychologists were trying to evaluate the constituent parts of human behaviour in an effort to make sense of it. There is, however, no clear definition of the concept (Rossetti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, what kind of causation could be at work here? This question comes up because we have argued that a reductionist account is blocked (Borsboom et al, 2019; Kalis, 2019). And second, how can folk psychological descriptions be shown to be correct or incorrect?…”
mentioning
confidence: 99%
“…Комментаторская историко-философская литература по теме насчитывает среди известных и влиятельных десятки источников (см., в частности, работы Криспина Райта). Однако и актуальное современное исследование «интенциональности» не обходится без ссылок на работы Витгенштейна (см., например: [Kalis, 2019]). Поэтому для историков философии закономерным становится вопрос о подходах к прочтению Витгенштейна: необходим ли исторический контекст (реконструкция критикуемых взглядов и концепций) или же лучшего понимания можно добиться в порядке актуализации заметок Витгенштейна по отношению к современным исследованиям по проблеме интенциональности (и пр.).…”
unclassified